Peningkatan Keterampilan Komunikasi Mahasiswa Calon Guru Melalui Kegiatan Analisis Artikel Ilmiah Dari Jurnal Nasional - Hikmawati Hikmawati; Haerunisyah Sahidu; Syahrial Ayub; Kosim Kosim (Unram Journal of Community Service, 2021)
The purpose of this service activity is to improve the communication skills of prospective teacher students through the analysis of scientific articles from national journals in Indonesia. This activity was carried out online from March to May 2021 as many as 12 meetings. Participants of this activity were 27 student teacher candidates from a university in the city of Mataram. The method of implementing this activity is: Students are given an explanation of the material at each meeting via the google meet platform. Students are given the opportunity to ask questions verbally. Students are assigned to search for scientific articles from national journals according to the topics discussed, this activity is carried out through google search. Students download scientific article files from national journals, then upload the file through the "Discussion Forum" feature prepared on the LMS (Learning Management System) platform. Furthermore, students discuss with group members according to discussion instructions through the "Discussion Forum" feature. The value of communication skills is obtained based on the observations of observers on student discussion activities on the "Discussion Forum" feature using a scale of 5. The improvement in communication skills of prospective teacher students is seen from the increase in each indicator at meeting 1 and meeting 12. The results of the observations show the communication skills score of prospective teacher students at the first meeting it was 55 (poor category) while at the last meeting it was 80 (good category). The N-gain value was 57 which was in the medium criteria. Thus, there is an increase in the communication skills of prospective teacher students through the analysis of scientific articles from national journals